Предмет: Алгебра,
автор: igogo2004
(3х+4)(4х–3) – 17=(2х+3)(6х+7.
Ответы
Автор ответа:
1
(3x + 4)(4x - 3) - 17 = (2x + 3)(6x + 7)
12x² - 9x + 16x - 12 - 17 = 12x² + 14x + 18x + 21
7x - 29 = 32x + 21
7x - 32x = 21 + 29
-25x = 50
x = -2
Ответ: x = -2.
12x² - 9x + 16x - 12 - 17 = 12x² + 14x + 18x + 21
7x - 29 = 32x + 21
7x - 32x = 21 + 29
-25x = 50
x = -2
Ответ: x = -2.
Автор ответа:
0
Ответ: x=-2
Похожие вопросы
Предмет: Математика,
автор: belkinaanzelika26
Предмет: Биология,
автор: zakrevska78
Предмет: Алгебра,
автор: kirvskir00
Предмет: Математика,
автор: smurovmaks2